2021
DOI: 10.1021/acsami.1c05064
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole–Cyanobenzene Dyes Electrografted to Carbon or Indium-Doped Tin Oxide Supports for Visible Light-Driven Photoanodes and Olefin Isomerizations

Abstract: The organic carbazole−cyanobenzene push−pull dye 1,2,3,5tetrakis(carbazol-9-yl)-4,6-dicyanobenzene was derivatized and attached to carbon or indium-doped tin oxide (ITO) electrodes by simple diazonium electrografting. The surface-bound dye is active and stable for the visible light photosynthetic isomerization of a wide range of functionalized stilbene and cinnamic acid derivatives. Up to 87,000 net turnovers were obtained for the isomerization of trans-stilbene. The isomerizations can be carried out in air wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…A later study by Bergens and co-workers demonstrated the immobilization of 4CzIPN on carbon or indium tin oxide (ITO) surfaces using electrografting (Scheme ). The grafted 4CzIPN allowed for the conversion of trans - to cis -olefins via heterogeneous catalysis. The isomerization can be performed with 87 000 turnovers with the same catalyst prior to degradation and even performs well in air.…”
Section: E → Z Isomerization Of Olefinsmentioning
confidence: 99%
See 3 more Smart Citations
“…A later study by Bergens and co-workers demonstrated the immobilization of 4CzIPN on carbon or indium tin oxide (ITO) surfaces using electrografting (Scheme ). The grafted 4CzIPN allowed for the conversion of trans - to cis -olefins via heterogeneous catalysis. The isomerization can be performed with 87 000 turnovers with the same catalyst prior to degradation and even performs well in air.…”
Section: E → Z Isomerization Of Olefinsmentioning
confidence: 99%
“…Many deep-blue TADF emitters have sufficient ISC but slow RISC rates, leading to efficiency roll-off in the performance of OLED devices . Fortunately, the issue of trapped high-energy triplet states that plagues blue TADF OLEDs can instead be beneficial for EnT catalysis. , Recent reports also point toward supramolecular design strategies that improve ISC and limit RISC in TADF PCs: the construction of polymeric networks consisting of 4CzIPN emitters or emitters grafted onto ITO . These concepts are still in their infancy and merit further exploration.…”
Section: Strengths and Weaknesses Of Tadf Ent Pcsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] A certain number of important organic conversion reactions, such as photooxidation of alcohols, amines, and olens, have been successfully achieved through different semiconductor materials. [4][5][6][7][8] However, the application potential of semiconductor materials is limited due to their inefficient visible-light utilization and poor selectivity for the desired products. 9 Therefore, the development of new photocatalysts with a high efficiency and selectivity is essential for the conversion of organic chemicals.…”
Section: Introductionmentioning
confidence: 99%